Keterampilan Berpikir Tingkat Tinggi Siswa Dalam Pembelajaran Model Inkuiri Terbimbing Materi Sistem Koloid: Sebuah Studi Literatur - Rizki Anggi Suhairah Nasution; Zonalia Fitriza (Edukimia, 2021)
The purpose of this study was to describe students higher-order thinking skills in the guided inquiry learning model of the colloid system material. This research is library research using semi-systematic literature review type. The nature of this research is descriptive analysis. The data collection method in this research is the documentation method with the Miles and Huberman data analysis method. The experimental procedure used follows the following stages: 1) Designing a review, 2) Conducting a review, 3) Analysis, 4) Writing a review. The results of this study showed that students high-order thinking skills in guided inquiry model learning colloid system material can be seen in the exploration, concept formation, application, and closing stages.